A Pandemic Instrument Can Start Turning Collective Problems into Collective Solutions by Governing the Common-Pool Resource of Antimicrobial Effectiveness. (2022) - Weldon, Isaac; Liddell, Kathy; Van Katwyk, Susan Rogers; Hoffman, Steven J.; Minssen, Timo; Outterson, Kevin; Palmer, Stephanie; Viens, A.M.; Viñuales, Jorge
Abstract: To address the complex challenge of global antimicrobial resistance (AMR), a pandemic treaty should include mechanisms that 1) equitably address the access gap for antimicrobials, diagnostic technologies, and alternative therapies; 2) equitably conserve antimicrobials to sustain effectiveness and access across time and space; 3) equitably finance the investment, discovery, development, and distribution of new technologies; and 4) equitably finance and establish greater upstream and midstream infection prevention measures globally. Biodiversity, climate, and nuclear governance offer lessons for addressing these challenges.